Early jump-out corner detectors - Cooper, James (1993)
We present two new corner detectors; one works by using dissimilarity along the contour direction to detect curves in the image contour and the other estimates image curvature along the contour direction. These operators are fast, robust to noise and require no subjective threshholding.